Autonomy, eating disorders and elite gymnastics: ethical and conceptual issues - Andrew Bloodworth (Sport, Education and Society, 2017)
Participation in elite sport, and in particular those sports with special demands in terms of weight and shape, is associated with a higher risk for eating disorders such as anorexia nervosa [Sundgot-Borgen, J., & Torstveit, M. K. (2010). Aspects of disordered eating continuum in elite high intensity sports. Scandinavian Journal of Medicine and Science in Sports, 20, 112–121]. We report upon research exploring eating attitudes and behaviours within elite gymnastics. The study comprised 42 semi-structured interviews with gymnasts and support staff—34 gymnasts and 9 staff/support staff. The majority of those interviewed were acrobatic gymnasts (22; 16 males and 6 females) with 7 rhythmic gymnasts (all female) and 5 tumblers (all female). The mean age of those gymnasts interviewed was 17.4. A difficulty in precisely delineating extreme eating patterns (disordered eating) from having an eating disorder was noted. Within an elite sports context behaviours thought to be pathological in a more general setting might be fairly commonplace and even functional to the athlete's performance. The extent to which the athlete consents to these patterns of behaviour is problematic given their age and development. We argue that conceptualising consent as ‘authority to be cared for by a trustworthy coach’, more felicitously applies to the child/adolescent elite sporting context, helping us understand not only the focus of the elite gymnast, but also their relationship with the coach and the coaches' responsibilities.